Vesicular Systems Used for Wound Healing - Sally Abdelfattah; Maha Nasr; Abdelkader Ali; Ahmed Geneidi (Ain Shams University, 2021)
When the skin is injured through physical, chemical, mechanical, and/or thermal damage, a spontaneous series of events start to happen, often called the "cascade of healing," so as to restore the injured tissues, replace the damaged structures and prevent the invasion of pathogens into the damaged tissues. A number of traditional products are available for wound healing such as gels, creams, ointments, dressings and solutions, which depend mainly on moisture intake so as to help tissue repair, yet they do not provide optimal conditions to permit recovery of the wounds. Nanocarriers play a significant role in wound healing, since they are reported to improve drug delivery into the skin through alternation of pharmacokinetics and biodistribution of drugs, hence they increase bioavailability of drugs. Vesicular systems such as liposomes, niosomes, transfersomes, penetration enhancer containing vesicles (PEVs) and ethosomes are among the carriers proven to enhance the therapeutic action of drugs applied for wound healing. In this review, we summarize and discuss different vesicular systems used for wound healing, their composition, their advantages and disadvantages, their methods of preparation and their mechanisms of skin penetration.